Can bugs be an alternative or adjuvant to drugs in schizophrenia? - Mushraf Syed, Veena Nayak, Padmaja Ananth Shenoy (Journal of Applied Pharmaceutical Science, 2024)
Schizophrenia (SPR) pathophysiology is complex and uncertain, with growing evidence highlighting the role of gut microbiota (GM) in its etiopathogenesis. Trillions of gut bacteria are found to be influencing the brain by crossing the blood–brain barrier through various pathways. Gut dysbiosis in particular has been linked to SPR, which has opened up new avenues for the prevention and treatment of SPR by maintaining the gut bacterial diversity with the supplementation of living organisms in adequate proportions termed psychobiotics. In this paper, we reviewed the most shreds of evidence and concepts relating GM through the vagus nerve, neurotransmitters, and microbial by-products to various conceivable pathways leading to and ameliorating SPR. Both animal and human trials have been reviewed to discover the effects of probiotics in modulating endocrinal, inflammatory, immunochemical, and neuronal changes in modifying the physiological and psychopathological states of an individual, which assisted in identifying their physiological basis to improve mood and cognitive abilities and reduce anxiety in both healthy people and SPR patients. Currently, probiotic supplementation and faecal microbiota transplantation are the most recommended interventions. However, the present literature is scarce to conclude specific microbial species or probiotics that can benefit SPR through modification of the microbiota–gut–brain axis. Further evidence from the clinical trials is essential to discover novel gut microbial species that can maintain the diversity of the gut microbial population and benefit SPR disease.
Keywords: Probiotics, schizophrenia, gut microbiota, dysbiosis, microbiota-gut-brain axis, bugs